A comparative study of wave 1 and 2 mortality factors among COVID-19 patients in a level 3 medical college hospital in Saharanpur India - Devinder Kumar Vohra; Singh, Nawab; Manchanda JK; Sanjeev Davey; Arvind Trivedi; Anuradha Dave; Kayanat Nasser (Asian Journal of Medical Sciences, 2022)
Background: In COVID-19, second wave death rate climbed in several states of India including Uttar Pradesh with relatively high number of casualties as compared to first wave. The literature lacks scientific reason behind this. Aims and Objectives: The present study aimed toward detection of mortality factors for COVID-19 patients from a Level 3 Medical College Hospital in both waves in Western UP District in India so as to find a better treatment strategies for COVID-19 patients for possible next 3rd COVID-19 wave. Materials and Methods: This study is aimed to find any difference in Wave 1 and 2 mortality factors among COVID-19 patients in a Level 3 Medical College Hospital in western up district Saharanpur in India from April 1, 2020 to Sep 30, 2021. Results: Although there were more number of deaths in Wave 2 (n=537) as compared to Wave 1 (n=172), deaths even after treatment of COVID-19 were more in wave 1 (72%) as compared to wave 2 (67.9%), but it was not statistically significant (P>0.05). In COVID -19, Wave 1 most of the patients were elderly (aged >60 years) (40.3%) whereas in Wave 2 45–60 years age group were more affected (40.5%). Presence of more than 2 comorbidities was also seen more in wave 1 (37.1%) as compared to Wave 2 (23.8%). In COVID-19, both Waves (1 and 2) the most common co-morbidity was Type2DM (52% and 36.4%, respectively), but DM was found to be more in COVID+ve patients of Wave 1 as compared to wave 2 COVID+ve patients whereas any CARDIAC abnormality co-morbidity was found more in Wave 2 patients as compared to Wave 1 (14.2% vs. 12.1%). Conclusion: Possibly COVID-19 virus operated differently at Cardio-respiratory system leading to increased mortality in COVID-19 patients in Wave 2.